Usulan Penerapan E-Office Sebagai Upaya Transformasi Administrasi di Kwartir Cabang Gerakan Pramuka Kota Bogor - Hanisa Dwi Fitria; Rissa Ayustia (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2025)
The Bogor City Scout Movement Branch Office is still experiencing problems in administrative management, including cumbersome manual filing processes, unresponsive disposition of incoming letters, excessive paper consumption, and vulnerable financial document security systems. This research aims to propose the implementation of the E-Office system as an innovative solution for administrative transformation towards a more efficient and digitally integrated system. The research method used is a descriptive qualitative approach by collecting data from interviews with three key informants who have an active role in operations and administration at the Bogor City Scout Movement Branch. The results show that the use of E-Office has excellent potential to improve operational efficiency, increase document security, and speed up administrative processes. However, the implementation of E-Office requires special training and changes for employees who still use the manual system.